Click wave 1 - Abdulgaber, Karim ([Cairo] pyramids book centre, 2023)
Click wave provide the young learners with basics of how to use a computer and its compnents to know more about technology and how to have fun at this young age with it to motivate them to use it for greater purpose in the future
The world around us (computer)
Keywords: Computer Science